Onko uusyrittäjyyden luonne muuttunut?; Developments in New Entrepreneurial Activity in Finland - Annu Kotiranta; Mika Pajarinen; Petri Rouvinen (The Research Institute of the Finnish Economy (ETLA), 2016)
– About half of all new business activity in Finland can be categorized as being entrepreneurial. The number of this kind of new businesses has not increased dramatically during the last ten years. However, the characteristics of these businesses have changed. Nowadays, new entrepreneurs have higher education background, they have more likely work experience from a relevant field, they are more innovation-oriented, and they have higher initial growth aspirations. Their businesses are more likely to seek sales growth by utilizing international markets and by focusing more on consumer markets and less on business-to-business markets. On the other hand, maybe due to prolonged recession in the Finnish economy, the higher share of new entrepreneurial businesses is being started because there are no better opportunities to get a job. Heavy regulation and tight legislation are being seen as the most significant disincentives at the start-up phase. Growth-oriented new entrepreneurial firms see financial issues and labor market rigidities as significant restrictions for growth.
Keywords: D92; L26; L53; M13; 330; Entrepreneurship; Growth firm; Start-ups; Growth-orientation; Enterprise policy; Unternehmensgründung; Entrepreneurship; Mittelstandspolitik; Unternehmenswachstum; Unternehmenserfolg; Finnland